Two Previously Unrecorded Fungal Species Isolated from Muui Island in Korea - Soobin Shin; Hosung Jeon; Sieun Kim; Hyun-Ju Noh; Jong Won Jo; Kyunghun Min; Hokyoung Son (Mycobiology, 2023)
Fungi are cosmopolitan and they occupy diverse niches as consumers, producers, and decomposers. They play critical roles in the environment by enabling nutrient cycling and generating a plethora of secondary metabolites. This study aimed to identify and characterize fungal strains isolated from diverse sources on Muui Island, Republic of Korea. In 2023, a total of 86 fungal strains were collected and examined. Investigation of the morphological features and phylogenetic analyses of multiple barcode loci identified one putative novel species and two species previously unrecorded in the Republic of Korea: Colletotrichum sp., Colletotrichum guizhouense, and Fusarium brachygibbosum. This study provides a comprehensive description of their molecular phylogenies and morphological characteristics. These findings will contribute to the existing knowledge about fungal species in the Republic of Korea and future research on the fungal diversity on Muui Island.